The Royal Road to Peru. Vicissitudes of the communication system between the valleys and the Puna. 16th-18th centuries, Salta, Argentina (Quinto Sol, 2025)
This paper aims to investigate the changes and continuities in road networks during the colonial period in the Lerma Valley and its surroundings, in the province of Salta. To do so, it employs a multidisciplinary approach that ranges from understanding the reasons behind transit strategies between the 16th and 18th centuries to reconstructing the road system using a Geographic Information System (GIS). The analysis includes the evaluation of least-cost roads and a statistical comparison between them, in order to elucidate the evolution of communication routes in the colonial region.
Keywords: roads; valleys; hispanic period